Muslims In Pre-Modern Manipur: History, Economy And Society (Journal of Namibian Studies : History Politics Culture, 2022)
Manipur is a small State situated in the eastern most corner of India. It’s inhabited by several ethnic and religious communities. The valley of Manipur is inhabited by Meiteis/Meeteis, Manipuri Muslims, and several other small communities, while the surrounding hills are the homes of numerous tribes. As per the Census of 2011, the State has a Muslim population of 2.40 lakh, out of the State’s total population of 28.6 lakh.[i] Today, Muslims are spread mainly in the six districts of Manipur, namely Imphal East, Imphal West, Thoubal, Kakching, Bishnupur and Jiribam. Muslims of Manipuri origin are also found settled outside Manipur, particularly in Assam, Tripura, Bangladesh and even in Myanmar (erstwhile Burma). They migrated to these places, along with Meeteis, during the Burmese occupation of the valley of Manipur from 1819 to 1826. Cachar District of Assam has the largest concentration of Manipuri Muslims outside Manipur, with an estimated population of around 70-80 thousand.               The history of Muslims in Manipur is traced from around the middle of 16th century. They came from the west and settled in the valley by inter-marrying with the Meetei women. They are locally referred to as Pangals or Meitei-Pangals. Pangal is believed to be a corrupt word for Bengal, as majority of the Muslims came from Bengal. This paper makes an attempt to reconstruct the history, economy and society of the Muslims in Manipur in pre-modern times. The paper traces the historical circumstances that led to the settlement of Muslims, and also study their social formation, economic life and contributions, administrative and military engagements during the period under study. The local archaic manuscripts (puyas), mainly the royal chronicle, Cheitharol Kumbaba, Nongsamei Puya, Pangal Thorakpa, Khagemba Lanpha, Khagemba Langjei, etc., besides British colonial accounts, are used to primary sources.